Mispronouncing English Vowel Sounds on Office Admisintrative’s Students Universitas Bina Sarana Informatika - Wibowo, Ary Iswanto; Adi, Wiruma Titian; Pratama, Rizky Mirani Desi (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
The objective of this research is to figure out the mispronouncing English vowel sounds that are mostly made by University Students. The data were from 30 students of the Office-Administration Study Program Universitas Bina Sarana Informatika as the object of this research. The qualitative method is used for analyzing the recorded sounds that were produced by the students. The vowel sounds investigated in this research were sounds of [É‘Ë], [ÉœË], and [á´:]. The researchers gave 7 words each that contain the vowel sounds. The result indicated that most students produced the mispronouncing sound [á´:]. They often missed or slip between [É‘Ë] and [á´:]. This happened when the words tested were unfamiliar for the students.